Effects of Spring-Planted Cover Crops on Weed Suppression and Winter Wheat Grain Yield in Western Kansas - A. K. Obour; J. D. Holman; J. A Dille; V. Kumar (Kansas Agricultural Experiment Station Research Reports, 2019)
Herbicide resistant (HR) weeds pose a major challenge to continuous no-tillage (NT) dryland crop management systems. Integrating cover crop (CCs) in dryland crop rotations could suppress weeds and provide a weed management option for HR weeds in NT systems. Field experiments were conducted to investigate weed suppression potential of spring-planted CCs and their impacts on subsequent winter wheat grain yields. The CCs were oat/triticale, oat/triticale/pea, spring pea, and chem-fallow (standard) over 3 years and 2 locations in western Kansas. A weedy-fallow check was added to compare weed suppression of CCs in 2 out of the 3 years. Results showed CC mixtures of oat/triticale or oat/triticale/pea produced more biomass than spring pea by mid- June. Averaged across years, CC dry matter (DM) produced in Colby was 3560 lb/a with spring pea, 5850 lb/a for oat/triticale, and 5700 lb/a for the 3-way mixture of oat/triticale/pea. Similarly, DM production at HB Ranch (located 5 miles north of Brownell) was 2160 lb/a for spring pea, 4420 lb/a for oat/triticale or 4330 lb/a for oat/ triticale/pea. Regardless of study location, growing a CC resulted in>95% suppression of total weed biomass relative to the weedy-fallow check. Compared to chem-fallow, growing a CC reduced soil water content at winter wheat planting in 3 out of the 6 site-years (2017 at Colby, 2016 and 2017 at HB Ranch). At Colby, CCs reduced winter wheat grain yields in 2018 but not in 2016 or 2017. Except 2016, growing oat/triticale or oat/triticale/pea CC reduced wheat yields at HB Ranch. When averaged across the 3 years, wheat grain yields were 31 bu/a with chem-fallow, 30 bu/a after spring pea, and 34 bu/a with oat/triticale or oat/triticale/pea CC in Colby. Similarly, at HB Ranch, wheat grain yields averaged 50 bu/a with chem-fallow, 46 bu/a for spring pea, and 40 bu/a with either oat/triticale or oat/triticale/pea CCs.
Keywords: cover crops; weeds; dryland